The Impact of Authentic Leadership on Organizational Citizenship Behaviors: The Mediating Role of Affective‐ and Cognitive-Based Trust - Farid, Tahir; Iqbal, Sadaf; Khan, Asif; Ma, Jianhong; Khattak, Amira; Naseer Ud Din, Muhammad (Frontiers in Psychology, 2020)
Abstract Authentic leadership has appeared as a significant field of research. Building on social exchange theory that explicates how individuals mutually mechanize reciprocation and eventually establish a trust-based relationship, we postulated a positive relationship between authentic leadership and followers' organizational citizenship behaviors (OCB). Based on a two-wave time-lagged design, the data were obtained from 270 employees working in the private banking sector of Pakistan. We found that authentic leadership is positively associated with subordinate’s OCB, as well as, leads to a higher level of both affective and cognitive-based followers' trust. The results also indicated that both affective and cognitive-based trust positively mediated the relationship between authentic leadership and OCB. The implication for theory and practice are discussed.